Nicotine level associated with decreasing Treg number in smoker healthy volunteers - Akrom Akrom; Tri Julia Purnamasari; Zaky Nurfaiz; Adnan Adnan; Endang Darmawan; Muhammad Muhlis (International Journal of Public Health Science (IJPHS), 2021)
The intensity of cigarette exposure is associated with the severity of the inflammatory reaction. Treg cell plays a role in suppressing the inflammatory response. There has been no clear evidence on the relationship between smoker behavior with the nicotine level and Treg number. We will investigate the relationship between smoking behavior with the nicotine level and Treg number. We conducted a cross-sectional study of 106 healthy volunteers in Yogyakarta. We interviewed the subjects and took their blood samples for hemogram, Treg number, nicotine level, and blood chemistry examination. The inclusion criteria were fit, male or female, aged 18 years or older, and willing to volunteer proven by completing and signing the informed consent. We collected the data on smoking habits through interviews guided by a questionnaire. We examined hemogram and blood chemistry using a spectrophotometer, while the levels of nicotine were measured using The enzyme-linked immunosorbent assay (ELISA). We described the characteristics of the subjects by univariate analysis. The bivariate analysis was to determine the relationship between cigarette smoking length with nicotine level and Treg number. The results show a connection between the range of tobacco and cigarette number with nicotine levels in the blood with a value of r=0.63 in the Pearson correlation test p<0.00. It can be concluded that there is a relationship between behavior smoking with nicotine levels and Treg counts.